Synergistic Effects of Stirring and Aeration Rate on Carotenoid Production in Yeast Rhodotorula toruloides CCT 7815 Envisioning Their Application as Soap Additives - Renata M. M. G. P. Ribeiro; Bruno W. Picão; Daniele O. Gonçalves; Mateus Scontri; Vitor T. Mazziero; Cassamo U. Mussagy; Vijaya Raghavan; Carolina Astudillo-Castro; Andrés Córdova; Marcel O. Cerri; Elias B. Tambourgi (Fermentation, 2023)
The production of carotenoids by microbial organisms has gained significant interest due to the growing demand for natural products. Among the non-model oleaginous red yeasts, Rhodotorula toruloides stands out as an appealing host for natural carotenoid production. R. toruloides possesses the natural ability to metabolize a wide range of substrates, including lignocellulosic hydrolysates, and convert them into lipids and carotenoids. In this study, we focused on utilizing xylose, the main component of hemicellulose, as the major substrate for R. toruloides. We conducted a comprehensive kinetic evaluation to examine the impact of aeration and agitation on carotenoid production. Results in stirred-tank reactor demonstrated that under milder conditions (300 rpm and 0.5 vvm), R. toruloides accumulated over 70% of its cell mass as lipids. Furthermore, the highest carotenoid yields were achieved at high agitation rates (700 rpm), with carotenoid levels reaching nearly 120 µg/mL. Several carotenoids were identified, including β-carotene, γ-carotene, torularhodin, and torulene, with β-carotene being the major carotenoid, accounting for up to 70% of the total carotenoid content. The carotenoid-rich extract produced by R. toruloides under evaluated conditions was successfully incorporated into soap formulations, demonstrating the addition of antioxidant properties. This work provides a comprehensive understanding of xylose conversion into natural carotenoids by R. toruloides, presenting a promising avenue for their application in cosmetics. Furthermore, this study highlights the potential of a renewable and cost-effective approach for carotenoid production in the soap industry.